Surface-active ionic liquids in micellar catalysis: impact of anion selection on reaction rates in nucleophilic substitutions - Cognigni, Alice (Royal Society of Chemistry, 2016)

(untitled) (Phys Chem Chem Phys)
A series of surface-active ionic liquids based on the 1-dodecyl-3-methylimidazolium cation and different anions such as halides and alkylsulfates was synthesized. The aggregation behavior of these ionic liquids in water was characterized by surface tension, conductivity measurements and UV-Vis spectroscopy in order to determine the critical micelle concentration (CMC) and to provide aggregation parameters. The determination of surface activity and aggregation properties of amphiphilic ionic liquids was accompanied by SAXS studies on selected surface-active ionic liquids. The application of these surface-active ionic liquids with different anions was tested in nucleophilic substitution reactions for the degradation of organophosphorus compounds. Kinetic studies via UV-Vis spectrophotometry showed a strong acceleration of the reaction in the micellar system compared to pure water. In addition, an influence of the anion was observed, resulting in a correlation between the anion binding to the micelle and the reaction rate constants, indicating that the careful choice of the surface-active ionic liquid can considerably affect the outcome of reactions.